2018
DOI: 10.11621/pir.2018.0306
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance and Intolerance for Uncertainty as Predictors of Decision Making and Risk Acceptance in Gaming Strategies of the Iowa Gambling Task

Abstract: Background. This article reports on the results of an empirical study of interrelationships between indicators of decision-making strategies (indexed by the Iowa Gambling Task, IGT) and traits of tolerance and intolerance for uncertainty that capture the unity of cognitive and personality components of situational representations.Objective. Our study tested the hypothesis that overcoming uncertainty in decision making goes beyond cognitive representations of the task but instead is rooted in the construction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 13 publications
0
11
0
2
Order By: Relevance
“…Persons who report higher UT are more likely to report lower negative affect and higher life satisfaction (Garrison et al, 2017), as well as higher self-esteem and creativity (Pavlova, 2018). Higher UT also appears to be associated with greater risk-taking (Kornilova et al, 2018), whereas lower UT and lower tolerance for ambiguity has been associated with behavioral outcomes indicative of risk aversion (Tsui, 1993; Kornilova et al, 2018). UT appears positively related to adaptability and adaptive readiness (Shamionov, 2017), and more specifically with the ability to cope constructively with chance events (Kim et al, 2016).…”
Section: Theoretical Gapsmentioning
confidence: 99%
“…Persons who report higher UT are more likely to report lower negative affect and higher life satisfaction (Garrison et al, 2017), as well as higher self-esteem and creativity (Pavlova, 2018). Higher UT also appears to be associated with greater risk-taking (Kornilova et al, 2018), whereas lower UT and lower tolerance for ambiguity has been associated with behavioral outcomes indicative of risk aversion (Tsui, 1993; Kornilova et al, 2018). UT appears positively related to adaptability and adaptive readiness (Shamionov, 2017), and more specifically with the ability to cope constructively with chance events (Kim et al, 2016).…”
Section: Theoretical Gapsmentioning
confidence: 99%
“…Personal Decision-Making Factors Questionnaire (LFR-21) developed by Kornilova [ 30 ]. The questionnaire consisted of 21 yes-or-no statements divided into two scales: (1) rationality, an inclination for a broader orientation in the decision situation, and (2) personal risk-readiness, willingness and ability to make and perform choices in uncertain situations.…”
Section: Methodsmentioning
confidence: 99%
“…New questionnaire of tolerance/intolerance for uncertainty (NTN) developed by Kornilova [ 30 ]. The questionnaire consisted of 33 statements, evaluated with a seven-point Likert scale (from “completely disagree” to “completely agree”).…”
Section: Methodsmentioning
confidence: 99%
“…Literature generally showed that uncertainty correlates with students' academic performance negatively. For instance, Kornilova et al [9] tested 60 typically developing adults and examined the contribution of tolerance/intolerance for uncertainty. The result showed that tolerance of uncertainty contributes to risk in decision making after trial failure, potentially limiting learning in uncertain conditions through risk aversion.…”
Section: Uncertainty and Academic Performancementioning
confidence: 99%